A Predictive Role of Autoantibodies Against the Epitope aa168–183 of ENO1 in the Occurrence of Miscarriage Related to Thyroid Autoimmunity - He, Xiaoqing; Liu, Yifu; Wang, Haoyu; Sun, Wei; Lu, Yihan; Shan, Zhongyan; Teng, Weiping; Li, Jing (Frontiers in Immunology, 2022)
Abstract Objective: To study the association between the serum levels of autoantibodies against one important epitope (168FMILPVGAANFREAMR183, designated as P6) of α-enolase (ENO1-P6Abs) and miscarriage among euthyroid females with thyroid autoimmunity (TAI). Methods: Anti-ENO1-P6 total IgG was investigated in 432 euthyroid women, and its four subclasses were analyzed in 184 euthyroid women. The serum FT4, TSH, TgAb and TPOAb levels were determined using an electrochemiluminescence immunoassay. The serum ENO1-P6Ab and anti-protein disulfide isomerase A3 autoantibody (PDIA3Ab) levels were determined using enzyme-linked immunosorbent assay . Results: The serum levels of anti-ENO1-P6 total IgG, IgG2, IgG3 and IgG4 were significantly higher in euthyroid TAI females than non-TAI controls. Additionally, anti-ENO1-P6 total IgG and its 4 subtypes were all markedly higher in euthyroid TAI females with pregnancy loss than those without miscarriage. Moreover, logistic regression analysis showed that highly expressed anti-ENO1-P6 total IgG and IgG1, IgG2, IgG3 subtypes in the serum were all independent risk factors for euthyroid TAI-related miscarriage, and its IgG1 was also for non-TAI-related abortion. According to the trend test, the prevalence of miscarriage was increased in a titer-dependent manner with the raised levels of serum anti-ENO1-P6 total IgG and IgG1, IgG2, IgG3 subtypes among euthyroid TAI females. The receiver operating characteristic curve analysis of anti-ENO1-P6 total IgG and IgG1, IgG2, IgG3 subclass expressions in the serum for miscarriage prediction in euthyroid TAI females exhibited that total areas under the curves were 0.773±0.041, 0.761±0.053, 0.827±0.043 and 0.760±0.050, respectively (all P<0.0001). Their corresponding optimal cut-off OD450 values were 0.68 (total IgG), 0.26 (IgG1), 0.97 (IgG2) and 0.48 (IgG3), with sensitivities were 70.8%, 87.5%, 83.3% and 85.4%, and specificities were 70.8%, 59.1%, 77.3% and 56.8%, respectively. There was an additive interaction between serum anti-ENO1-P6 and anti-PDIA3 total IgGs on the development of miscarriage (RERI=23.6, AP=0.79, SI=5.37). Conclusion: The highly expressed ENO1-P6Abs may be important risk factors for euthyroid TAI-related miscarriage. The serum levels of ENO1-P6Abs may become good predictive markers for pregnancy loss in euthyroid TAI females, especially its IgG2 subclass expression.